Energy Consumption for Nutrient Removal from High-Nitrate and High-Phosphorus Wastewater in Aerobic and Anaerobic Bioelectrochemical Reactors - Joanna Rodziewicz; Artur Mielcarek; Kamil Bryszewski; Wojciech Janczukowicz; Karolina Kłobukowska (Energies, 2022)
An attempt was undertaken to determine indicators of energy consumption in bio-electro reactors (BERs) i.e., an aerobic rotating electrobiological disc contactor (REBDC) and an anaerobic sequencing batch biofilm reactor (SBBR), during contaminant removal from soilless tomato cultivation wastewater having a specific composition, i.e., high nitrate and phosphorus concentrations and low COD. Because of this specificity, the energy consumption during the treatment process was characterized by a cumulative indicator for simultaneous removal of phosphorus and nitrates—EEINUTRIENTSrem (electric energy consumption per unit of removed nutrient load, expressed as kWh/kgNUTRIENTSrem). Four values of direct current density were tested: 0.63, 1.25, 2.5, and 5.0 A/m2. The indicator values were compared at a hydraulic retention time (HRT) of 24 h. The study demonstrated that the values of electric energy consumption per unit of removed nutrient load determined in the anaerobic SBBR ranged from 30 to 464 kWh/kg NUTRIENTSrem and were lower than the values obtained in the aerobic REBCD, i.e., 80–1380 kWh/kg NUTRIENTSrem.